A Companion to the City. - Bridge, Gary (Blackwell companions to geography., 2008)
A Companion to the City provides the reader with an indispensable and authoritative overview of the key debates, controversies, and questions concerning the city from a variety of theoretical vantage points with an international perspective.:.; Indispensable companion for students of the City.; Multidisciplinary approach of interest across several fields.; Includes contributions from major scholars in the field.